Do Computerized Delivery Systems Promote Less Pain and Anxiety Compared to Traditional Local Anesthesia in Dental Procedures? A Systematic Review of the Literature - França, Arthur José Barbosa de; Barbirato, Davi da Silva; Vasconcellos, Ricardo José de Holanda; Pellizzer, Eduardo Piza [UNESP]; Moraes, Sandra Lúcia Dantas de; Vasconcelos, Belmiro Cavalcanti do Egito (Elsevier, 2022)
Purpose: The aim of this study is to assess whether the use of computerized devices to deliver local anesthesia results in less pain and anxiety compared to traditional anesthesia in adult dental procedures. Methods: This review was registered at PROSPERO (CRD 42021265046), based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and was structured according to the PICO strategy. The studies were selected based on eligibility criteria, and data were collected by 1 author and reviewed by another. Results: Nine of the 10 studies included were randomized controlled trials. Differences related to pain and anxiety were observed, which favored computerized techniques; however, caution should be exercised when interpreting these results due to differences in assessment methods. The studies used different local anesthetics, including 2% lidocaine, 4% articaine, or 3% mepivacaine with epinephrine diluted 1:80,000 to 1:200,000. A total of 560 patients were evaluated. Conclusions: Computerized anesthesia devices yielded better results than conventionally delivered anesthesia after qualitative evaluation. Nevertheless, conventional anesthesia is widely used, safe, and effective. Due to the heterogeneity among the included studies, it is strongly recommended that new randomized clinical trials using well-defined methodologies be performed to improve the quality of evidence regarding this topic.